2015
DOI: 10.7314/apjcp.2015.16.16.6941
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and Attitude of Nurses in Regard to Providing Hospice Care

Abstract: Background: Awareness and attitudes of nurses regarding end of life care are important factors in providing hospice care. In an extensive literature review, we found no related articles investigating Iranian nurses awareness and attitudes about providing such care. Objectives: The aims of this study were to investigate the awareness and attitudes of Iranian nurses in providing hospice care. Materials and Methods: In this descriptive-correlational study, 240 nurses employed in six educational centers were selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
(17 reference statements)
1
4
0
Order By: Relevance
“…So, these results are consistent with our results and approve that many nurse still have a lot of uncertainties about the positive effects of pain control medications. This finding is consistent with other studies that showed the quality of different aspect of daily living in cancer patients is low (Abbasnezhad et al, 2015;Aghdam et al, 2015;Faghani et al, 2015;Fathollahzade et al, 2015;Ghasempour et al, 2015;Tahory et al, 2016).…”
Section: Discussionsupporting
confidence: 93%
“…So, these results are consistent with our results and approve that many nurse still have a lot of uncertainties about the positive effects of pain control medications. This finding is consistent with other studies that showed the quality of different aspect of daily living in cancer patients is low (Abbasnezhad et al, 2015;Aghdam et al, 2015;Faghani et al, 2015;Fathollahzade et al, 2015;Ghasempour et al, 2015;Tahory et al, 2016).…”
Section: Discussionsupporting
confidence: 93%
“…Finally, perceived benefits had an indirect effect on practices. This phenomenon manifests that although nurses can realize the benefit of patients receiving palliative care is that patients are able to die peacefully and had a good death with omnidirectional care, highlife quality, and dignity ( 30 ). The patient's religion and burial rites should be respected ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…This integration will lead to enhanced availability and improved outcomes (17,54). The results of recent research on PC also showed a need for HPC services in Iran, but since PC is an emerging approach, the HPC system establishment needs further research and preparation of facilities and requirements (10,14,41,42,53). However, from the experts' point of view, the implementation of the above actions will face limitations given that the PC system of Iran is still in its infancy.…”
Section: Discussionmentioning
confidence: 99%
“…In Jordan, 2 HPC service centers take advantage of specialists trained in other countries (40). In Iran, inadequate training and the lack of knowledge and experienced workforce in PC is one of the major challenges ahead (10,25,(41)(42)(43).…”
Section: Human Resource Developmentmentioning
confidence: 99%